2013
DOI: 10.1099/ijs.0.041889-0
|View full text |Cite
|
Sign up to set email alerts
|

Sinomicrobium oceani gen. nov., sp. nov., a member of the family Flavobacteriaceae isolated from marine sediment

Abstract: A marine bacterium, designated SCSIO 03483T, was isolated from a marine sediment sample collected from the Nansha Islands in the South China Sea. The strain produced roundish colonies with diffusible yellow-coloured pigment on nutrient agar medium or marine agar 2216. Optimal growth occurred in the presence of 0–4 % (w/v) NaCl, at pH 7.0 and a temperature range of 28–37 °C. 16S rRNA gene sequence analysis indicated that the isolate belonged to the family Flavobact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
31
0

Year Published

2013
2013
2015
2015

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(32 citation statements)
references
References 39 publications
(34 reference statements)
1
31
0
Order By: Relevance
“…The description is as given by Xu et al (2013) with the following amendments. Catalase and oxidase activities are variable among species.…”
Section: Emended Description Of the Genus Sinomicrobium Xu Et Al 2013mentioning
confidence: 99%
See 2 more Smart Citations
“…The description is as given by Xu et al (2013) with the following amendments. Catalase and oxidase activities are variable among species.…”
Section: Emended Description Of the Genus Sinomicrobium Xu Et Al 2013mentioning
confidence: 99%
“…The DNA G+C content of the type strain, SCSIO 03483 T , of a single species of the genus, Sinomicrobium oceani, isolated from an abyssal sediment sample of the South China Sea, was 38.4 mol% (Xu et al, 2013). In addition to this species, many members of the family Flavobacteriaceae have been isolated from marine environments, such as seawater, sediments, sponge and tidal flat sediment.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Preliminary sequence comparisons with 16S rRNA gene sequences deposited in the GenBank/EzTaxon-e (Kim et al, 2012) databases indicated that strain E403 T belonged to the family Flavobacteriaceae in the phylum Bacteroidetes. On the basis of 16S rRNA gene sequence similarity, type strains S. oceani SCSIO 03483 T (Xu et al, 2013), J. marina En5 T (Quan et al, 2008), Zhouia amylolytica HN-171 T (Liu et al, 2006) and Imtechella halotolerans K1 T (Surendra et al, 2012) shared 92.9, 92.4, 92.2 and 92.0 % sequence similarity with strain E403 T , respectively. In the neighbour-joining phylogenetic tree ( Fig.…”
mentioning
confidence: 99%
“…The cultural, physiological and biochemical characteristics of strain E403 T are given in the species description and in Table 1. (Xu et al, 2013, and this study); 3, J. marina En5 T (Quan et al, 2008, and this study). ND, Not detected; 2, for fatty acids, less than 1 % of the total fatty acids or not detected; V, variable, the API 20NE results were different to those of Biolog.…”
mentioning
confidence: 99%